Answer

Verified

372.9k+ views

**Hint:**This question is from the topic of algebra. We will factor the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\] by using rational root theorem. According to rational root theorem, first we will check the possibilities of roots of the equation. After getting the exact zeros, we will find the factors of the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\].

**Complete step by step answer:**

Let us solve this question.

The question is asking us to factor the given equation. The given equation is \[y={{x}^{3}}+4{{x}^{2}}-x-4\].

For finding out the factor of the equation, we will use rational root theorem.

The rational root theorem says that the zeros or the roots of any given function or equation is expressed in the form of \[\dfrac{p}{q}\], where p and q are integers. If we consider an example of an equation like:

\[y={{a}_{0}}{{x}^{n}}+{{a}_{1}}{{x}^{n-1}}+{{a}_{2}}{{x}^{n-2}}.............+{{a}_{n-1}}x+{{a}_{n}}\],

Then we can say that the values of p are factors of \[{{a}_{n}}\] and the values of q are the factors of \[{{a}_{0}}\] or we can say that p should be a divisor of constant term and q should be a divisor of coefficient of leading term.

So, the zeros of the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\] will be in the form of \[\dfrac{p}{q}\], where value of p is a factor of -4 and value of q is a factor of 1.

Hence, possibilities of zeros of the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\] will be

\[\pm 1\], \[\pm 2\], and \[\pm 4\].

Now, we will check the value of equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\] by putting the above values in place of x.

If the value of y is zero at any value, then it will be the root of the equation. And, if the value of y is not zero, then the term which we have put in place of x will not be the root of the equation.

Let us check the value of equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\] at x=-1.

\[y={{\left( -1 \right)}^{3}}+4{{\left( -1 \right)}^{2}}-\left( -1 \right)-4=-1+4+1-4=0\]

As the value of y is zero at x=-1. Then, -1 is a root or zero of the equation.

Now, let us check at x=1, we get

\[y={{\left( 1 \right)}^{3}}+4{{\left( 1 \right)}^{2}}-\left( 1 \right)-4=1+4-1-4=0\]

Hence, we get that x=+1 is a root of the equation.

Now, let us check at x=-2, we get

\[y={{\left( -2 \right)}^{3}}+4{{\left( -2 \right)}^{2}}-\left( -2 \right)-4=-8+16+2-4=6\]

Hence, x=-2 is not the root of the equation.

Let us check at x=+2, we get

\[y={{\left( +2 \right)}^{3}}+4{{\left( +2 \right)}^{2}}-\left( +2 \right)-4=8+16-2-4=18\]

Hence, x=+2 is not a root of the equation.

Now, let us check at x=-4, we get

\[y={{\left( -4 \right)}^{3}}+4{{\left( -4 \right)}^{2}}-\left( -4 \right)-4=-64+64+4-4=0\]

Hence, we get that x=-4 is the root of the equation.

Now, let us check at x=+4, we get

\[y={{\left( +4 \right)}^{3}}+4{{\left( +4 \right)}^{2}}-\left( +4 \right)-4=64+64-4-4=120\]

Hence, x=+4 is not the root of the equation.

Now, we have seen that -1, +1, and -4 is a root of the equation.

As x=-1 is root of the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\], then we can say that (x+1) is a factor of the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\].

Similarly, we can say that if x=+1 and x=-4 are roots, then (x-1) and (x+4) are factors of the equation.

So, we get that (x+1), (x-1), and (x+4) are the factors of the equation \[y={{x}^{3}}+4{{x}^{2}}-x-4\].

**Therefore, we can write the factors of equation as**

\[y={{x}^{3}}+4{{x}^{2}}-x-4=\left( x+1 \right)\left( x-1 \right)\left( x+4 \right)\].

\[y={{x}^{3}}+4{{x}^{2}}-x-4=\left( x+1 \right)\left( x-1 \right)\left( x+4 \right)\].

**Note:**We should have a better knowledge in algebra and polynomials to solve this type of question easily. We should know about the rational root theorem. As we have used rational root theorem in this question. This theorem can be used in any type of polynomial rather it satisfies the conditions. And, also remember that if any equation \[y={{a}_{0}}{{x}^{n}}+{{a}_{1}}{{x}^{n-1}}+{{a}_{2}}{{x}^{n-2}}.............+{{a}_{n-1}}x+{{a}_{n}}\] (lets, say) has a root that is \[{{x}_{1}}\], then \[\left( x-{{x}_{1}} \right)\] will be a factor of the equation \[y={{a}_{0}}{{x}^{n}}+{{a}_{1}}{{x}^{n-1}}+{{a}_{2}}{{x}^{n-2}}.............+{{a}_{n-1}}x+{{a}_{n}}\]

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail